Influence of circumferential ankle pressure of shoe collar on the kinematics, dynamic stability, electromyography, and plantar pressure during normal walking. - Alireza Nasirzadeh; Seung-Tae Yang; Juseok Yun; Jaeha Yang; Young Yoon Bae; Juyeon Park; Jooeun Ahn; Giuk Lee (PLoS ONE, 2023)
Background The shoe's collar plays a significant role in supporting the ankle during walking. Since the protective effect of the collar requires the circular embracing of the ankle and shank, a stiffer collar might be involved with increased circumferential ankle pressure (CAP). It is not clear how collar CAP affects walking performance. Therefore, this study was aimed at examining the influence of the collar CAP on the kinematics, dynamic stability, electromyography (EMG), and plantar pressure during normal walking. Method Sixteen healthy male participants walked on a treadmill while wearing a custom-designed high-collar shoe with 10 (low), 30 (medium), and 60 mmHg (high) CAP conditions, and the joint angles, dynamic stability index, EMG, and plantar pressure were measured. Result While the low CAP condition did not affect the ankle range of motion (ROM), The high CAP condition restricted both the ankle sagittal and frontal ROM, whereas the medium CAP condition limited only the ankle frontal ROM. The knee and hip ROM did not differ between conditions. The dynamic stability for the high and medium CAP cases was comparable but significantly higher than that of the low CAP condition. The ankle muscle activity and corresponding co-contraction increased with increasing CAP for gastrocnemius medialis (GM), soleus (SOL), peroneus longus (PL), tibialis anterior (TA) muscles in the weight acceptance and push-off phases but not in the single limb support. Knee muscle activity, including vastus lateralis (VL) and semitendinosus (SEMI) was similar between all conditions. A higher relative pressure was observed under the lateral aspect of the heel when walking in the high CAP condition. Conclusion The results suggest that a high-collar shoe with a high CAP may not be an appropriate choice for walking owing to the injury risk factors and limited walking efficiency. A medium CAP is associated with certain advantages and, thus, a superior choice for high-collar shoe design.